2013
DOI: 10.1364/ol.38.004671
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-wideband three-dimensional optoacoustic tomography

Abstract: Broadband optoacoustic waves generated by biological tissues excited with nanosecond laser pulses carry information corresponding to a wide range of geometrical scales. Typically, the frequency content present in the signals generated during optoacoustic imaging is much larger compared to the frequency band captured by common ultrasonic detectors, the latter typically acting as bandpass filters. To image optical absorption within structures ranging from entire organs to microvasculature in three dimensions, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…Higher resolution might be achieved with optoacoustic tomography, as seen in Figure 1B-D where Razansky et al [34] show how MSOT can be used to resolve fluorophores in the brain of an adult transgenic zebrafish in vivo with a scalable spatial resolution of a few tenths of microns. In addition, Gateau et al have shown that 3D optoacoustic tomography enables imaging depths of several millimeters to centimeters with scalable resolution under $100 mm [35]. Even higher resolution can be obtained, as shown by Omar et al, by making use of an ultra-wideband single element transducer with a bandwidth of 20-180 MHz [36], demonstrating an axial resolution of $4 mm and a lateral resolution of $18 mm for imaging depths up to 5 mm, allowing imaging of vascular structures under the skin or in small-animal model systems.…”
Section: Optoacoustic Imagingmentioning
confidence: 99%
“…Higher resolution might be achieved with optoacoustic tomography, as seen in Figure 1B-D where Razansky et al [34] show how MSOT can be used to resolve fluorophores in the brain of an adult transgenic zebrafish in vivo with a scalable spatial resolution of a few tenths of microns. In addition, Gateau et al have shown that 3D optoacoustic tomography enables imaging depths of several millimeters to centimeters with scalable resolution under $100 mm [35]. Even higher resolution can be obtained, as shown by Omar et al, by making use of an ultra-wideband single element transducer with a bandwidth of 20-180 MHz [36], demonstrating an axial resolution of $4 mm and a lateral resolution of $18 mm for imaging depths up to 5 mm, allowing imaging of vascular structures under the skin or in small-animal model systems.…”
Section: Optoacoustic Imagingmentioning
confidence: 99%
“…The experimental setup used in this study is based on a translate-rotate geometry previously described [11,12]. Figure 1(a) shows a schematic of the system.…”
Section: Optoacoustic Experimental Setupmentioning
confidence: 99%
“…Data sets were obtained by employing a rotation range of 178.5° and a fixed translation range for each of the transducer arrays employed (Table 1). This translation range ensured a good coverage of the sample in planes transversal to the detection probe (perpendicular to the z-axis) and enabled to obtain a homogeneous resolution over the covered scanning area [12,16]. The scanner allowed imaging biological samples contained in a cylinder of 10 mm diameter and 10 mm height.…”
Section: Acquisition Procedures and Scanning Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…While broad-band detection can be achieved with polyvinylidene-fluorid-based (PVDF) hydrophones, for the most sensitive PZT transducers, the BW is typically on the same order of magnitude as the center frequency, resulting in narrow bandwidths, especially if highly sensitive detection of frequencies below 10 MHz is required. In photoacoustic imaging, artifacts are created by the simultaneous detection of small and large structures, where both high-and low-frequency spectral components are integrated for image reconstruction [8,9]. Therefore, a sensor with a high sensitivity to low-and high-frequency spectral components would be best suited for PAI.…”
Section: Introductionmentioning
confidence: 99%